Род тахициксиус — Tachycixius W. Wgn. (Homoptera, Cixiidae) — и описание двух новых видов из СССР - Логвиненко, В.Н. (Вестник зоологии, 1971)
Tachycixius tigrinus sp. n. described from the Crimea, Eastern Georgia, Azerbaijan Daghestan and Turkmenia has much in common with T. desertorum (Fieb.) , but it is well distinguished from the latter by a longer motile tooth of the penis tunica and pre scnce of the serrate distension in the distal segment base. The species — T. bifurcatus sp. n. from the Nakhichevan Autonomous SSR is very close to T. viperinus D l a b. It has the following typica peculiarities: rudimentary teeth of penis tunica, twin-cone motile teeth in the distal segment base, bifurcated middle tooth and as distinct from T. vipernus D l a b — a wide lobate anal tube appendage.